C.06 Retraction of scientific publications in neurosurgery. (2nd June 2017) - Wang, JZ; Alotaibi, NM; Ku, J; Rutka, JT
Abstract : Background: Despite increasing awareness of scientific fraud, no attempt has been made to assess its prevalence in neurosurgery. The aim of our review was to assess the chronological trend and reasons for the retraction of neurosurgical publications.Methods: We searched the EMBASE and MEDLINE databases using a comprehensive search strategy for retracted articles from January 1995 to December 2016. Archives of retracted articles onwww.retractionwatch.com and the independent websites of neurosurgical journals were also searched. Data including the journal name and its impact factor, reason for retraction, country of origin, and citations were extracted.Results: A total of 72 studies were included for data extraction. Journal impact factor ranged from 0.24 to 14.4. Most studies(76%) were retracted within the last 5 years. The most common reason for retraction was because of a duplicated publication found elsewhere(25%), followed closely by plagiarism(21%), or falsifying data(17%). Other reasons included scientific errors/mistakes, author misattribution, and fraudulent peer review. Articles originated from several different countries and some were widely cited.Conclusions: Retractions of neurosurgical publications are increasing globally, mostly due to issues of academic integrity. Implementation of more transparent data sharing and screening as well as additional education for new researchers may help mitigate these issues moving forward.